The Impact of Technology Adaptation on Academic Engagement: A Moderating Role of Perceived Argumentation Strength and School Support - Zhao, Jing; Awais-E-Yazdan, Muhammad; Mushtaque, Iqra; Deng, Limei (Frontiers in Psychology, 2022)
The COVID-19 pandemic has impacted routine activities such as attending to school and transferring education online. This study explores students' perceptions of technology adoption and academic engagement using data from a survey (N = 465), with perceived argumentation and school support serving as moderators. The data were collected using a convenience sampling technique. The authors examined the association between perceived utility, perceived digital competitiveness, and perceived ease of use and academic engagement. While perceived utility and ease of use of online learning technologies do not appear to be connected with academic engagement, digital competence is. Academic involvement has no effect on perceived reasoning power, but social support has a considerable effect on academic engagement.